231k views
16 votes
Solve the system of equations y=-x+3 and 2x+2y=6

User Johan G
by
4.4k points

2 Answers

4 votes

Answer:

Answer to the first equasion is y=2: 2=-1+3

Explanation:

y=-x+3 (x=1)

-3 y=-x

-3=2

2=-1+3

y=2

Hope this helps and makes sence

User Judine
by
4.9k points
8 votes

Answer:

y = -x + 3

Explanation:

1. Substitute "y = -x + 3" in for y in the second expression:

2x + 2(-x + 3) = 6

2. Simplify:

2x + (-2x) + 6 = 6

0 + 6 = 6

6 = 6

Because the values are equal, the solution of y = -x + 3 is a valid input.

hope this helps!

User Guinn
by
5.1k points